Case Report: Diagnosis of Primary Cutaneous Amyloidosis Using Dermoscopy and Reflectance Confocal Microscopy - Wang, Xiuli; Wang, Hui; Zhong, Zhenyu; Zheng, Liyun; Wang, Yifan; Guo, Ze; Li, Hui; Gao, Min (Frontiers in Medicine, 2021)
The dermoscopy and reflectance confocal microscopy (RCM) can provide new insights for diagnosis disease as non-invasive and easy-to-use tool. We described the dermoscopy and RCM characteristics of two patients with primary cutaneous amyloidosis (PCA) respectively. The dermoscopy characteristics were as follows: brownish macules with brown or white centers surrounded by hyperpigmented blotches, and a whitish scar-like center encircled by irregular brownish hyperpigmented spots or patches. The RCM features were increased melanin deposition in the basal layer, highly refractive structures with various shapes in the enlarged papillary dermis, and the increased pleomorphic structure of the dermal papillary ring. This is the first report the dermoscopy and RCM characteristics of PCA. We hope the characteristic dermoscopy and RCM appearances would provide a basis for doctors to diagnose and intervene earlier.